THE MOTIVE OF NATURE AS MIRROR OF AUTHOR’S «EGO» IN M. M. PRISHVIN’S BOOK «THE EYES OF THE EARTH» (Филологический класс, 2017)
In this article the motive of nature as mirror of author’s ego in the final book of M. M. Prishvin, which was made during the process of handling his late diary notes, is analyzed. Thematically, the motive demonstrates different «stages» of the spring awakening of nature. We consider the language of this awakening, incarnated in the favorite author’s form of lyrical miniature, which synthesizes an impression, experience, contemplation in itself. Specifying the logic of Prishvin’s genre intellection, we appeal to his theoretical reflection, which allows us to understand the interaction of diary notes and artistic text. The specialty of Prishvin’s miniatures is born by a combination of traits of realistic specifics in picturing of nature and metaphorism, which demonstrates his philosophizing over existence. The modeling of author’s «ego» grows because of the author’s ability to see a personal origin, correlating the life of his soul to it, realizing it in innermost origins. One of such origins is the first love, which «grows the whole person». At the same time, the reflection over mental depths is combined with the attention to «usual» rhythm of existence, demonstrated by the poetics of superstitions.